Using meshless methods to simulate the free vibrations of the cupula under pathological conditions - Santos, C.F. (2019)
Each canal of the vestibular system of the inner ear is composed of a circular path of continuum fluid. Inside each semicircular canal, it is possible to find a cupula, a gelatinous body contain-ing sensory hair cells, and the focus of this work. One of the causes of vestibular disorders is the abnormal concentration of otoconia particles near the cupula. The accurate determination of the natural frequency (first vibration frequency) of the cupula would allow to know which external frequency could be induce to stimulate externally the cupula. Thus, theoretically, the resonance effect would induce physical vibra-tion to the cupula and disperse the otoconia particles, reducing the vertigo symptoms. Hence, in this wok, two-dimensional and three-dimensional geometrical models of the cupula were constructed. Then, a free vibration analysis was performed using three distinct numerical techniques, the Finite Element Method (FEM), and two meshless methods: the Radial Point Interpolation Meshless Method (RPIM) and the Natural Neighbour Radial Point Interpolation Method (NNRPIM).